Osmotic Stress Confers Enhanced Cell Integrity to Hydrostatic Pressure but Impairs Growth in Alcanivorax borkumensis SK2 - Scoma, Alberto; Boon, Nico (Frontiers in Microbiology, 2016)
Alcanivorax is a hydrocarbonoclastic genus dominating oil spills worldwide. While its presence has been detected in oil-polluted seawaters, marine sediment and salt marshes under ambient pressure, its presence in deep-sea contaminated environments is negligible. Recent laboratory evidences highlighted the piezosensitive nature of some Alcanivorax species, whose growth yields are highly impacted by mild hydrostatic pressures (HPs). In the present study, osmotic stress was used as a tool to increase HP resistance in the type strain A. borkumensis SK2. Control cultures grown under standard conditions of salinity and osmotic pressure with respect to seawater (35.6 ppt or 1136 mOsm kg-1, respectively) were compared with cultures subjected to hypo- and hyperosmosis (330 and 1720 mOsm kg-1, or 18 and 62 ppt in salinity, equivalent to brackish and brine waters, respectively), under atmospheric or increased HP (0.1 and 10MPa). Osmotic stress had a remarkably positive impact on cell metabolic activity in terms of CO2 production (thus, oil bioremediation) and O2 respiration under hyperosmosis, as acclimation to high salinity enhanced cell activity under 10MPa by a factor of 10. Both osmotic shocks significantly enhanced cell protection by reducing membrane damage under HP, with cell integrities close to 100% under hyposmosis. The latter was likely due to intracellular water-reclamation as no trace of the piezolyte ectoine was found, contrary to hyperosmosis. Notably, ectoine production was equivalent at 0.1MPa in hyperosmosis-acclimated cells and at 10MPa under isosmotic conditions, supporting the hypothesis that ectoine synthesis may be primarily triggered by HP rather than osmotic stress. While stimulating cell metabolism and enhancing cell integrity, osmotic stress had always a negative impact on culture growth and performance. No net growth was observed during 4-day incubation tests, and CO2:O2 ratios and pH values indicated that culture performance in terms of hydrocarbons degradation was lowered by the effects of osmotic stress alone or combined with increased HP. These findings confirm the piezosensitive nature of A. borkumensis, which lacks proper resistance mechanisms to improve its metabolic efficiency under increased HP, thus explaining its limited role in oil-polluted deep-sea environments.